Bioanalytical Method Development and Validation for Quantitative Estimation of Valsartan by LC-MS/MS in Human Plasma - Chinthala, Krishna; Kancherla, Prasad; Kumar, Pramod (Asian Journal of Chemistry, 2017)
An accurate, precise LC-MS/MS method has been developed and validation for quantitative estimation of valsartan using irbesartan as internal standard in human plasma. The method was established based on the HPLC separation on Zorbax SB-C18, 4.6 × 50 mm, 5 μm (Make: Agilent technologies) column at 40 °C using HPLC methanol: 0.1 % formic acid (80:20, v/v) at a flow rate of 1 mL/min. The total chromatographic run time was 2.5 min with retention time of 1.40 min for valsartan. All quality control samples of analytes and internal standard was detected with LC-MS/MS system in multiple reactions monitoring mode. The method was validated according to USFDA guidelines. The calibration curves obtained were found to be linear over the concentration range of 50.85 to 12046.60 ng/mL. Recovery studies were conducted for spiked plasma samples and mean % recoveries were ranged from 75.39-79.44 %. The results of within the batch and between the batch precision and accuracy were found within the limits of acceptance. The proposed LC-MS/MS method can successfully applied for the pharmacokinetic studies.